The neurobiology of openness as a personality trait - Abu Raya, Maison; Ogunyemi, Adedoyin O.; Broder, Jake; Carstensen, Veronica Rojas; Illanes-Manrique, Maryenela; Rankin, Katherine P. (Frontiers in Neurology, 2023)
Openness is a multifaceted behavioral disposition that encompasses personal, interpersonal, and cultural dimensions. It has been suggested that the interindividual variability in openness as a personality trait is influenced by various environmental and genetic factors, as well as differences in brain functional and structural connectivity patterns along with their various associated cognitive processes. Alterations in degree of openness have been linked to several aspects of health and disease, being impacted by both physical and mental health, substance use, and neurologic conditions. This review aims to explore the current state of knowledge describing the neurobiological basis of openness and how individual differences in openness can manifest in brain health and disease.